Social Conditioning of the Internet Development - Ljajic, Samir H (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Technology is not a self-contained product that arises in a social vacuum, it arises in a certain relationship with a society, thus the development of electronic communications technologies is conditioned by social transformations that have opened up space for the development of these technologies. Therefore, Internet represents an answer to certain social processes and in our fluid life an individual becomes the center of the mediated model of sociability. Using Habermas's typology of social action, interpersonal media are classifiedas informational-collaborative, sociable, expressive and strategic, and modern society and the use of Internet condition their transmission and procreative role. Historians and sociologists insist on the structure-related divisions and those that bring about change. Thus, on the one hand, it is argued that neither computers nor literacy are harmful, but that there are consequences for those who use them. Language theory insists that the text does not exist by itself but is a product of readers' interpretations, the same way media do not reflect reality but actively work to create it. In the era of planetary explosion, the subcultures and identities of the  modern Internet generations have become multifaceted, multilingual and transcultural. Thus, our understanding of the Internet as media must be complex, too. Therefore, despite knowledge democratization and its availability through the Internet, one must not neglect that fundamental social role of media springs from their manipulative power, based on strategies of production and control of the symbolic potentialsof society.
Keywords: Internet; society; social conditions; media; information and communication technologies; manipulation